2008
DOI: 10.1111/j.1743-6109.2008.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle-Related Changes in Circulating Androgens in Healthy Women With Self-Reported Normal Sexual Function

Abstract: Introduction There is currently neither a clinically useful, reliable and inexpensive assay to measure circulating levels of free testosterone (T) in the range observed in women, nor is there agreement on the serum free T threshold defining hypoandrogenism that is associated with female-impaired sexual function. Aim Following the Clinical and Laboratory Standards Institute guidelines, we generated clinically applicable ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 56 publications
3
25
0
1
Order By: Relevance
“…The effect of menopause on sexual function is a relatively wellstudied subject in female sexual response compared with the premenopausal period (20)(21)(22)(23)(24) Regarding the relationship between menstruation and sexual function, some investigators found that the phases of the menstrual cycle had an effect on sexual function in women with type 1 diabetes (25,26). Some investigators studied the possible relationship between irregular menstruation and sexual dysfunction in premenopausal women without systemic disease (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of menopause on sexual function is a relatively wellstudied subject in female sexual response compared with the premenopausal period (20)(21)(22)(23)(24) Regarding the relationship between menstruation and sexual function, some investigators found that the phases of the menstrual cycle had an effect on sexual function in women with type 1 diabetes (25,26). Some investigators studied the possible relationship between irregular menstruation and sexual dysfunction in premenopausal women without systemic disease (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, both androgens and estrogens play an important role in female sexual arousal, motivation, and activity [12,15]. In most cases, increased androgens such as dehydroepiandrosterone (DHEA), dehydroepiandrosterone sulfate (DHEAS), androstenedione and/or testosterone favor sexual arousal [29-32], but this relationship may be age, concentration and cycle-phase dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, female sexual function has been shown to increase during the ovulatory phase of the menstrual cycle, in congruence with rising free and total testosterone [12]. This is in opposition to the work of Battaglia et al [13], who report no significant variation in androgens across the cycle but mention that additional synthesis and metabolism at the adrenal glands and peripheral tissues make it difficult to accurately correlate a specific androgen to sexual function.…”
Section: Introductionmentioning
confidence: 99%
“…Although estrogen receptor and P receptor are expressed in both the epithelial and stromal compartments of endometrium, AR expression is confined to human endometrial stromal cells (HESCs) (5,6). Serum androgen levels fluctuate throughout the menstrual cycle, with levels peaking around the time of ovulation (7,8). On the other hand, tissue androgen levels and conversion of androstenedione to T are higher in secretory than in proliferative endometrium (9).…”
mentioning
confidence: 98%